KONSEP HARTA DAN KEPEMILIKANNYA MENURUT HUKUM ISLAM - Irwansyah Irwansyah (Universitas Islam Negeri Ar-Raniry, 2018)
Property is a primary need for humans to support life in this world, so as to carry out worship to Allah swt well. Nevertheless, the Qur'an warns that property must be obtained in a desired manner of Islamic law, and are used in places that have goodness according to Islamic law required. A principle developed by Islamic law to the problem of property is the rules do not set definitely in the Quran and Hadis, but the general principles are put forward, which must be followed by everyone who tried to get the property. islamic law requires in acquiring and managing property to note of the following principles; 1) property acquired and owned is not of the type that is unclean and dangerous to humans; 2) the way to obtain the property is done by humane methods, such as buying and selling is done by the parties by not deceive one another, bless one another and be honest when covenant; 3) as the party who has the authority to carry out property, Islamic law mentioned basic requirements that need to be considered, namely a maximum adult age (minimum 18 years) and has a ruysd (smart) characteristic, that is the ability to carry out property in accordance with the rule of Islamic law. By following all the things that have been mentioned, then property can be valued provides benefit to humans, both in keeping religion or maintaining the human body and soul (mukallaf).